2012
DOI: 10.1007/s10856-012-4703-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of hydroxyapatite nanoparticles on osteosarcoma cells and osteoblasts

Abstract: The effects of hydroxyapatite nanoparticles (HA-NPs) on two kinds of cells, human MG63 cells and the normal osteoblasts were investigated. According to the MTT assay and fluorescent staining assay, it was proved that HA-NPs could inhibit the growth of MG63 cells but slightly support proliferation of the osteoblasts. Meanwhile, transmission electron microscopy (TEM) was employed to observe the ultrastructural alterations of both cells. The TEM results showed that HA-NPs had entered the two kinds of cells. Typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 12 publications
4
52
0
Order By: Relevance
“…Interestingly, cytotoxic effects were observed with increasing HAPna concentration to 1.0 mg/mL HAPna. HAP cytotoxicity has been reported previously (Qing et al, 2012;Sun et al, 1997), in particular Sun et al, (1997) demonstrated that osteoblast cellular proliferation was significantly reduced when cultured in media containing HAP powder at a concentration of 1.0 mg/mL, as was used in this study, thus highlighting the importance of testing nanoparticle concentrations over a narrow range of the desired concentration to assess potential toxicity (Sun et al, 1997).…”
Section: Cytocompatibility Assessment Of Hydroxyapatite Hydrogel Scafsupporting
confidence: 66%
“…Interestingly, cytotoxic effects were observed with increasing HAPna concentration to 1.0 mg/mL HAPna. HAP cytotoxicity has been reported previously (Qing et al, 2012;Sun et al, 1997), in particular Sun et al, (1997) demonstrated that osteoblast cellular proliferation was significantly reduced when cultured in media containing HAP powder at a concentration of 1.0 mg/mL, as was used in this study, thus highlighting the importance of testing nanoparticle concentrations over a narrow range of the desired concentration to assess potential toxicity (Sun et al, 1997).…”
Section: Cytocompatibility Assessment Of Hydroxyapatite Hydrogel Scafsupporting
confidence: 66%
“…The potential toxicity or biocompatibility of HA particles depends on their concentration. In a study by Qing et al, 42 it was found that concentrations of HA nanoparticles ranging from 100 to 500 µg/mL reduce the growth and the viability of MG-63 cells. At a concentration of 100 µg/mL, HA nanoparticles are found in cell lysosomes, and concentrations greater than 250 µg/mL causes apoptotic changes in the nuclei of MG-63 cells.…”
mentioning
confidence: 99%
“…HA nanoparticles suspended in a cell culture medium slightly support the proliferation of primary human osteoblasts but inhibit the growth of MG-63 cells and induce apoptosis in this cell type. 42 Previously, composites 0, N2-N25, and M2-M5 were tested for mechanical properties, 22 aimed at finding a suitable ratio of HA nano/microparticles to optimize the mechanical properties to be comparable with that of human cortical bone. The modulus of elasticity in bending of the composites is similar to that in cortical bone, which is 14-20 GPa.…”
mentioning
confidence: 99%
“…Ultrasonic enhanced hydroxyapatite into cells, and increased the intracellular HA concentration, then the tumor can be inhabited by low HA concentration. HA can be dissolved at the aid environment, the phosphate radical and calcium ion release of HA, resulting the increase of the intracellular calcium concentration, and induced the tumor cell apoptosis [20,21] . Beyond that, HA can affect the function of organelles in cytoplasm, cell cycle block, the inhibition of telomerase activity , mitochondrial function injury, DNA damage, and protein synthesis [22,23] .…”
Section: Discussionmentioning
confidence: 99%